Nutrient content, fiber fractions, and rumen fermentation in vitro of mulato grass grown with different cutting age in lowland West Java, Indonesia - Mayasari, Ph.D, Novi; Salman, Lia Budimulyati; Susilawati, Iin; Sandrawati, Apong; Ismiraj, Muhammad Rifqi; Firmansyah, Indra; Wulansari, Asri (Fakultas Peternakan, Universitas Padjadjaran, 2025)
One of the major challenges in ruminant production in Indonesia is ensuring the availability of high-quality and adequate forage. Identifying forage varieties with good nutritive value that adapt well to local climate conditions is crucial. This study evaluated the nutrient composition, fiber fractions, and in vitro rumen fermentation of Mulato grass harvested at different cutting ages (30, 40, and 50 days) in the lowlands of West Java, Indonesia. The nutrient content, analyzed using proximate and fiber fraction analysis, showed no significant differences across cutting ages except for ash content, which was lower at 40 days. Mulato grass cut at 30 days had lower acid detergent fiber (ADF), neutral detergent fiber (NDF), acid detergent lignin (ADL), and hemicellulose levels, while its cellulose content was higher compared to grass cut at 40 or 50 days. Rumen fermentation results indicated that grass cut at 30 days had higher in vitro dry matter digestibility (IVDMD), organic matter digestibility (IVOMD), and total volatile fatty acids (TVFA). These findings suggest that Mulato grass harvested at 30 days offers better digestibility and rumen fermentation outcomes, making it a suitable forage choice for ruminants in the lowlands of West Java, Indonesia.